2016
DOI: 10.1080/10412905.2016.1185471
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of native and naturalizedLamiaceaespecies growing in the Patagonia region (Argentina)

Abstract: Argentina, include one species of oregano, Origanum vulgare L., three naturalized species of mint, Mentha rotundifolia L., M. pulegium L. and M. spicata L., and two native species, Clinopodium darwinii (Benth.) Kuntze and Scutellaria nummulariifolia Hook. f.According to Zuloaga and Morrone (1) there are three Mentha species in Argentina (perennial and adventitious), two of them grow in the Patagonia, Mentha spicata L. in the provinces of Chubut, Neuquén, Río Negro, but also grows in other provinces of Argentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Previous research has reported that the genus Origanum exhibits two chemotypes with different concentrations of monoterpenes, such as terpinen-4-ol, cis-and trans-sabinene hydrate, carvacrol, and thymol [32][33][34][35][36]. e variability in essential oil composition of O. vulgare L. is due to diverse subspecies as well as different ecological and climatic parameters [6,37,38].…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…Previous research has reported that the genus Origanum exhibits two chemotypes with different concentrations of monoterpenes, such as terpinen-4-ol, cis-and trans-sabinene hydrate, carvacrol, and thymol [32][33][34][35][36]. e variability in essential oil composition of O. vulgare L. is due to diverse subspecies as well as different ecological and climatic parameters [6,37,38].…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…The herb is carminative, stomachic, and antispasmodic; given to stop hiccups, flatulence, colicky pains, cholera, etc. (Chowdhury et al, 2007) EOs: carvone (49.62%-76.65%), limonene (9.57%-22.31%), 1,8-cineole (1.32%-2.62%) (Chauhan et al, 2009); p-cymene, isopiperitone, piperitone, dihydroedulan II, menthone, p-cymen-8-ol, β-linalool (Cirlini et al, 2016); carvone (40.8%) and limonene (20.8), 1,8-cineole (17.0%), β-pinene (2.2%) (Snoussi et al, 2015); carvone (34.0-70.4%), isodihydrocarvyl acetate (0.5%-13.4%), limonene (11.7%-16.4%) (Retta et al, 2017); carvone (57.1%), limonene (10.1%), cis-dihydrocarvone (3.2%), dihydrocarveol (3.2%), germacrene D (3.1%), 1,8 cineole (2.9%) (Chauhan, Nautiyal, & Tava, 2010); carvone (59.50-63.24%), limonene (9.09-10.44%), and 1,8-cineol (4.51-6.36%) (Hussain et al, 2010); carvone (73.29%), limonene (7.59%), dihydrocarvone (3.83%), α-bourbonene (1.67%), and trans-sabinenehydrate (1.57%) (Chowdhury et al, 2007); eucalyptol (46.28%), 1,3,5-tri-methyl-6-methylene-cyclohexene (19.25%), and caryophyllene (5.47%) (Park et al, 2016); carvone (48.60%), cis-carveol (21.30%), and limonene (11.30%) (Govindarajan, Sivakumar, Rajeswari, & Yogalakshmi, 2012); carvone (49.5%) and menthone (21.9%) (Soković et al, 2009); carvone (78.76%), limonene (11.50%) and…”
Section: Grandifloramentioning
confidence: 99%
“…EOs: β-caryophyllene (26.67%), germacrene D (12.31%), carveol (7.38%), pulegone (32.09%), piperitenone oxide (17.28%), and 5-acetyl thiazole (11.26%) (Riahia et al, 2013); 2,4(8),6-p-menthatrien-2,3-diol (14.5%) and germacrene D (12.4%) (Pino, Rosado, & Fuentes, 1999); piperitenone oxide (58.7%), piperitone oxide (15.9%), terpinen-4-ol (6.3%), and pulegone (3.9%) (Fatiha et al, 2016a); piperitenone oxide (75.6-68.7%), trans-caryophyllene (5.2%), and germacrene D (7.1%) (Retta et al, 2017); phenolic compounds and flavonoids: quercitrin, caftaric, gentisic, caffeic, p-coumaric, chlorogenic acids, rutin, isoquercitrin, luteolin, and apigenin (Moldovan et al, 2014); apigenin, isoquercetin, epicatechin, quercetin 3-O-galactoside, luteolin, chlorogenic acid, cyaninchlorid, myrtillin, quercetin, rutin, caffeic acid, ferulic acid, hydroxybenzoic acid, p-coumaric acid, rosmarinic acid, syringic acid, transcinamaldehyde acid, and vanilic acid (Siham, Rachid, & Al-Zoubi, 2019).…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulegone, isopulegone, piperitone, piperitenone, piperitenone oxide, menthone, isomenthone and menthol are the main constituents. 1,8-Cineole, menthofuran, carvacrol, thymol, linalool and their derivatives can also seldom be found [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The second group is decidedly less common, and includes species like Clinopodium umbrosum (M.Bieb.)…”
Section: Discussionmentioning
confidence: 99%